Proceedings of 3rd International Conference on the Industry 4.0 Model for Advanced Manufacturing AMP 2018 (Lecture Notes in Mechanical Engineering, 2018)
This book presents the proceedings of the 3rd International Conference on the Industry 4.0 Model for Advanced Manufacturing (AMP 2018), held in Belgrade, Serbia, on 5-7 June 2018, the latest in a series of high-level conferences that brings together experts from academia and industry to exchange knowledge, ideas, experiences, research findings, and information in the field of manufacturing. The book addresses a wide range of topics, including, for example, design of smart and intelligent products, developments in CAD/CAM technologies, rapid prototyping and reverse engineering, multistage manufacturing processes, manufacturing automation in the Industry 4.0 model, cloud-based products, and cyber-physical and reconfigurable manufacturing systems. By providing updates on key issues and recent advances in manufacturing engineering and technologies, it aids the transfer of vital knowledge to the next generation of academics and practitioners. It appeals to anyone working or conducting research in this rapidly evolving field.